If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (x)(x) Multiply x * x x = x2 Solving x = x2 Solving for variable 'x'. Combine like terms: x2 + -1x2 = 0 x + -1x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(1 + -1x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {0, 1}
| 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 | | F(x)=5x^2+6x-8 | | -10.6x+5.6x=40 | | 18x-10-6w=50 | | -5(3d+8)=35 | | -4m+2-4m+12= | | 4(u-9)= | | F(x)=5(90)-100 | | 75=5(x)-100 | | =(3x^3-7x^2+5x-9)-(7x^3-7x^2-4x+4) | | F(x)=5(75)-100 | | 4x-4-7x-10= |